Screening of bioantagonistic bacteria for biocontrol agent of Rhizoctonia solani and surfactin producer - YULIAR YULIAR (Society for Indonesian Biodiversity, 2008)
The objective of this research was to screen 31 of bacteria isolates that have potency to control Rhizoctonia solani growth and isolates capability to produce surfactin. R. solani growth inhibition was performed uses paper discs containing a 5 days cultivation of isolates culture. Surfactin activity assay was performed on LB agar medium. Results of the screening showed that the highest growth inhibition was obtained for isolates code 54 (96.43%), KC4 (93.45%), and 163 (93.19%). All of the isolates were cooproducer of surfactin and iturin, and the highest biosurfactan index was obtained for isolate KB2 (3.91).The four potential isolates were identified, as Bacillus pantotheinticus (isolate 54 and isolate 163), Bacillus brevis (isolateKC4), and Bacillus sp(isolate KB2).Â© 2008 Jurusan Biologi FMIPA UNS SurakartaKey words: biocontrol, Bacillus pantotheinticus, Bacillus brevis, Bacillus sp., Rhizoctonia solani, surfactin